The community of tragedy. Georges Bataille and "the Thirties" (Nóema, 2013)
Tragedy became the explicit focus of only a few essays by Georges Bataillle. In spite of this fact, tragedy is one of his most enduring speculative obsessions, especially during his violent intellectual experiences in the Thirties. The brilliance of a tragically wasted self is the dark side of each self-exposing singularity. The real tragic gesture, the one that gives a structure to community, is the sacrifice of Orestes fleeing the Furies. In the depths of despair he bites and tears a finger from his left hand, thus causing the collapse of his personal consistency. Such gesture potentially infects the other singularities, thus becoming able to build together a tragic community.
Keywords: Bataille; tragedy; community